Pattern of ocular morbidities among preschool children of Biratnagar Metropolis of Nepal - Chaudhary, Neha Priyadarshani; Badhu, Badri Prasad; Parajuli, Surya Bahadur; Dev, Barun (Birat Journal of Health Sciences, 2022)
Introduction: Children use their vision to enhance motor skills, develop parent–child bonds, build picture perception, and gain balance. Children may enter school with vision problems. Sub-optimal vision can lead to poor academic performance, a lack of interest in school, and even dropping out. Objective: To evaluate the pattern of various ocular morbidities among preschool children of Biratnagar metropolis. Methodology: A cross sectional study was conducted from October 2020 -Jan 2021 among 393 study participants at 5 different preschools of Biratnagar using total enumeration sampling. Vision was assessed with Snellen’s visual acuity charts and Kay Picture chart. Anterior and posterior segment examination was done using a hand-held portable slit lamp and a direct ophthalmoscope respectively. Binocularity was assessed with a cover test at a distance and near targets and the Hirschberg corneal reflex. The refractive status of the eyes was assessed by performing static retinoscopy. All the data was analyzed according to sex, age, causes of visual impairment and types of ocular morbidity. Results: Among the total 393preschool children screened, 169 children were boys and 224 were girls. The prevalence of ocular morbidity was found to be 20.1 %. Refractive error was the most common cause of visual impairment which was seen in 14.7% of children. The overall prevalence of myopia, hyperopia, and astigmatism was 7.9%, 4.8%, and 2.1% respectively. The other types of ocular morbidities were strabismus in 1.3%, congenital cataract in 1%, conjunctivitis in 1%, chalazion in 1.3%, vernal keratoconjunctivitis in 1% and congenital ptosis in 0.6%. Conclusion: The relatively high prevalence of refractive error and occurrence of other ocular morbidities in our studied population suggests that there is a need for a large-scale community-based preschool screening program in Nepal so that affected preschool children can be identified early and appropriate treatment can be promptly started.